Adapting an online screening tool for major depressive disorder in South Africa - Hassem, Tasneem (My University, 2022)
Depression has become a global concern as 300 million people are estimated to suffer from depression globally. In South Africa, the life-time prevalence of depression is estimated at 9.7%. As a result of the severity of depression in South Africa and the lack of accessible and accurate depression screening instruments, the study followed a sequential exploratory mixed method design which was conducted as a phased approach in order to adapt an online depression screening tool which is easy to use and culturally appropriate for the South African public. Phases One and Two utilised a systematic review methodology in order to determine the availability of online depression screening tools for the general public of South Africa and to explore the ethical considerations associated with online psychological screening tools. The results obtained from Phase One and two were used to inform Phase Three which consisted of the tool adaptation. The Center for Epidemiological Studies Depression Scale-Revised (CESD-R) was deemed the most appropriate depression screening for adaptation. Items of the CEDS-R were adapted in terms of language used; some items were removed and items specific to the South African context were added. The adapted screening tool was placed on an open access depression screening website (mddsa.co.za). The final phases of this study involved assessing the validity and reliability of the tool. A purposive sample of 50 healthcare professionals assessed the content validity using the Consensus-based Standards for the selection of health Measurement Instruments (COSMIN) method. These results were used to further refine the online adapted tool in terms of the relevance and comprehensiveness. In order to determine the content validity ratios of the online adapted CESD-R, 21 experts in the field were approached to rate each item on the tool. Overall, content validity ratios indicate good content validity for all 19 items. Criterion validity was assessed using a sample of 86 individuals from the general public and 21 3 patients diagnosed with MDD. Using the Receiver Operating characteristic Curve (ROC) procedure, the sensitivity and specificity of the tool was determined. A sensitivity score of 90.48% and a specificity score of 47.67% were obtained for the tool. In addition, the tool evidenced an Area Under the Curve (AUC) of 0.78, indicating the tool is fairly accurate. In conclusion, online mental health screening tools have the possibility to facilitate mental health care and access. In addition, the online adapted CESD-R can be used as an adjunct tool in the healthcare sector as a first step in helping individuals identify their symptoms and actively seek help. The instant feedback received on the completion of the tool can be viewed as the first step in the individual actively seeking formal treatment and care.
A thesis submitted to the Faculty of Humanities in fulfilment of the requirement for the degree of Doctor of Philosophy, University of the Witwatersrand, Johannesburg